Expansive Units in the Field of Polish Kinematic Phraseology to Denote Emotions - Lozynska, Oksana (Respectus Philologicus, 2024)
The article belongs to a series of publications devoted to the study of the peculiarities of the functioning of Polish kinematic phraseological units (hereinafter KPhU) denoting emotions. The purpose of the article is to demonstrate the peculiarities of the functioning of the expansive changes in the analysed KPhU. The result of the analysis is a thorough examination of 34 expansive units (created as a result of modifying the structure and/or semantics of 19 out of 418 analysed normative kinematic phraseological units (KPhUs), recorded in 565 contexts), revealing the peculiarities of their formation and use, as well as an attempt to determine the reasons for their appearance. It is concluded that the identified expansive changes in the analysed normative KPhU, given their increasing frequency, may eventually become a phraseological norm. The reason for their emergence and spread is the pressure of the system on the norm, the protective function of which is significantly weakened in conditions where the main sphere of functioning of the KPhU is the spoken language.
Keywords: Polish phraseology; phraseological innovations; expansive phraseological units; linguistic norm; usage